Produção de informaçãoo estatística oficial na (des)ordem social da modernidade - Porcaro, Rosa Maria (1999)
This study deals with the big changes that characterize today s society and how they affect the relevance of official statistics which are brought together under the Statistical Information System. Our society s configuration is examined under three different approaches: the Information Society, the Post-Fordism Society and the Post-Modern Society. It is argued that the changes pointed out by the interpretative frame of these three different approaches can not be captured with the conceptual-methodological framework used by the Statistical Information System, tailored to fit the Industrial Capitalist Society, greatly modified nowadays. The study reveals that certain non-material phenomena, central to our society s concerns cultural, knowledge-related, informational, sign & image formed are not included in (covered by) the Statistical Information System or are included from the standpoint of the "materially oriented Industrial Capitalist Society, having as a consequence the misrepresentation of these phenomena